Penerapan Model Pembelajaran Kooperatif Tipe Course Review Horay (CRH) untuk Meningkatkan Minat Belajar Ilmu Pengetahuan Alam dan Sosial - Eri Nuraeni (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This research is based on students' low interest in learning in Natural and Social Sciences (IPAS) subjects, which can be seen from the large number of students who obtain scores below the Learning Goal Achievement Criteria (KKTP). The focus of this research is to increase students' interest in learning through the application of the Course Review Horay (CRH) learning model in the material "Style Around Us", as well as analyzing changes in students' learning interest after using this model. The aim of this research is to describe the implementation of the Course Review Horay (CRH) learning model in science learning and identify the increase in students' interest in learning after its implementation. The method used was Classroom Action Research (PTK) using the Kemmis & McTaggart model, which was carried out in two cycles with four meetings. The subjects of this research were 23 class IVB students of Madrasah Ibtidaiyah Ziyadatul Iman. Data collection techniques include observation, interviews, documentation and questionnaires. The research results show an increase in students' interest in learning in each cycle. The percentage of filling out the questionnaire in the pre-cycle was 2, increased to 3.1 in cycle I, and reached an average of 4.04 in cycle II with an increase of 0.6. Based on these results, the application of the Course Review Horay (CRH) learning model has been proven to increase students' interest in learning in science subjects. Therefore, it is hoped that this model can be applied in learning science and other subjects.